The Effect of the Dose of Herbal Supplements In Feed on The Growth And Survival Rate of Asian Redtail Catfish (Hemibagrus nemurus) - Ahmad Nurul Fikri; Usman M Tang; Mulyadi Mulyadi (Jurnal Akuakultur SEBATIN, 2023)
This research aim to determine the optimal dose of additional herbal supplements in feed toward the growth performance and survival rate of red tilapia (Oreochromis niloticus) by using recirculation system. This research was conducted on November 01-December 10, 2021 at Laboratory of aquaculture technology, Marine and Fisheries Faculty, University of Riau. This research was using experimental method by completely random design (RAL) one factor with three replications. The treatments were: A: 0 mL/kg of feed (control), B: 50 mL/kg of feed, C: 75 mL/kg of feed, and D: 100 mL/kg of feed. The herbal supplements were consisted of turmeric, and ginger with Bacillus sp. and yeast (Rhizopus oligosporus). The results showed that a different doses of additional herbal supplements affecting the growth performance and the survival rate of catfish using recirculation system. In addition, it also affected the absolute weight growth, absolute length growth, feed efficiency and feed conversion ratio.The optimal dose was at 100 mL/kg of feed as it showed significantly different results compared to control. So that while being applied in terms of economy, 100 mL/kg was the most efficient dose, by giving the specific growth rate was 1,55%, survival rate was 98,3%, absolute weight growth was 8,67 g, absolute length was 6,23 cm, feed efficiency was 79,53% and feed conversion ratio was 1,26.